Osteogenesis imperfecta and pregnancy: A case report - Borde, Maia (2019)
Osteogenesis imperfecta (OI) belongs to the group of rare diseases due to its low incidence in the world population. It is a disorder which involves an inadequate bone formation that, from the clinical point of view, mainly leads to pathological fractures caused by extremely brittle bones. This frequently causes affected people to have a limited quality of life because of deformities and disability. Before birth, there are both invasive and noninvasive procedures that allow us to diagnose the disorder at early gestational ages. This is the case of a 35-year-old patient treated at the Hospital de Rivera, who had OI type IV and was pregnant with her second child. The same condition was suspected prenatally in the baby and subsequently confirmed at birth.